2016
DOI: 10.1038/srep27822
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide detection of CNVs in Chinese indigenous sheep with different types of tails using ovine high-density 600K SNP arrays

Abstract: Chinese indigenous sheep can be classified into three types based on tail morphology: fat-tailed, fat-rumped, and thin-tailed sheep, of which the typical breeds are large-tailed Han sheep, Altay sheep, and Tibetan sheep, respectively. To unravel the genetic mechanisms underlying the phenotypic differences among Chinese indigenous sheep with tails of three different types, we used ovine high-density 600K SNP arrays to detect genome-wide copy number variation (CNV). In large-tailed Han sheep, Altay sheep, and Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 62 publications
4
78
0
1
Order By: Relevance
“…Moioli et al performed a genome-wide scan using approximately 50 000 SNP, and detected BMP2 and VNRT genes related to fat deposition in sheep tails [70] . Through a genome-wide high-density SNP study of sheep with three tail types, Zhu et al detected several regions with CNVs harboring functional genes associated with fat deposition, such as PPARA, RXRA and KLF11 [71] . Furthermore, Yuan et al applied selection tests based on 50K SNP genotype data, and showed that HOXA11, BMP2, PPP1CC, SP3, SP9, WDR92, PROKR1 and ETAA1 genes may be involved in the formation of fat tails in sheep [72] .…”
Section: Tail Traitsmentioning
confidence: 99%
“…Moioli et al performed a genome-wide scan using approximately 50 000 SNP, and detected BMP2 and VNRT genes related to fat deposition in sheep tails [70] . Through a genome-wide high-density SNP study of sheep with three tail types, Zhu et al detected several regions with CNVs harboring functional genes associated with fat deposition, such as PPARA, RXRA and KLF11 [71] . Furthermore, Yuan et al applied selection tests based on 50K SNP genotype data, and showed that HOXA11, BMP2, PPP1CC, SP3, SP9, WDR92, PROKR1 and ETAA1 genes may be involved in the formation of fat tails in sheep [72] .…”
Section: Tail Traitsmentioning
confidence: 99%
“…In 2013, Liu et al analyzed 329 individuals of three sheep breeds (Sunit, Dubois, and German meat sheep) using SNP50 chips for sheep and detected 238 CNV regions, including 73 CNV regions with frequencies greater than 3% [9]. In 2016, Zhu et al [10] found that genes such as PPARA, RXRA, and KLF11 were related to fat deposition and affected the tail type of sheep. These CNV regions contain a large number of genes associated with fat metabolism and GTPase activity.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 90 CNVRs were detected across all the individuals, which represented the commonly shared CNVRs. A total of 55,44,82,15,14,72,190,18, and 5 CNVRs were detected as line-speci c CNVRs in line 6 3 , 7 2 , F 1 , RCS-A, D, J, L, M, and X, respectively, as compared to other lines (Table1, Additional le 6: Table S5). Importantly, the line 6 3 and 7 2 lineage-speci c CNVRs could potentially offer certain clues to explore the genetic mechanisms of MD resistance or susceptibility.…”
Section: Shared Versus Line-speci C Cnvrsmentioning
confidence: 99%
“…Following the rst two genome-wide scans for CNVs in human genome [7,8], an large number of CNV detection studies have been performed, which revealed that CNVs are ubiquitously distributed in the genome and can in uence the phenotype via regulations of gene expression and gene dosage [9][10][11]. Besides, numerous studies in other species have also shown that CNVs contributed to phenotypic variation of complex diseases and traits [12][13][14][15][16][17][18][19], including MD in chicken [20][21][22]. Two major traditional platforms employed in CNV detection are based on SNP chips, one is known as comparative genomic hybridization (CGH) array, and the other is SNP genotyping array.…”
Section: Introductionmentioning
confidence: 99%